2004
DOI: 10.1080/00926230490262366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Erectile Dysfunction (ED) on Sexual Life of Female Partners: Assessment with the Index of Sexual Life (ISL) Questionnaire

Abstract: Using the Index of Sexual Life (ISL) questionnaire specifically designed to measure the impact of erectile dysfunction (ED) on female partners' sexuality, we demonstrated that ED has a negative impact on the sexual life of female partners, specifically on their sexual satisfaction and sexual drive. Further analyses showed lower sexual satisfaction and sexual drive for women reporting a disturbance or change in their own sexual lives than for women who did not. Older women had lower scores compared to younger w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 9 publications
6
66
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The majority of the women, whose partners were treated with PDE5i for 6 months, experienced improvements in their own sexual function, a finding that accords with earlier studies. 12 However, as reported in earlier papers, those that recorded lower levels of functioning on the FSFI were not necessarily dissatisfied with their partners' treatment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] The majority of the women, whose partners were treated with PDE5i for 6 months, experienced improvements in their own sexual function, a finding that accords with earlier studies. 12 However, as reported in earlier papers, those that recorded lower levels of functioning on the FSFI were not necessarily dissatisfied with their partners' treatment.…”
Section: Discussionsupporting
confidence: 80%
“…[1][2][3][4][5][6][7][8] Treatment of men with ED with oral phosphodiesterase type 5 inhibitors (PDE5i) has also been reported to have positive benefits for their female partners. [9][10][11][12] Most of these studies have relied on standardized sexual function (for example, Female Sexual Function Index (FSFI)) 13 and treatment satisfaction questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Further, after the treatment of ED, these females showed significant improvements in their sexual functioning. Chevret et al 19 also showed that ED had a negative impact on the sexuality of female partners. Female partners (n ¼ 376) of men with ED evidenced lower levels of sexual satisfaction and sexual desire than female partners (n ¼ 345) of men who did not have ED.…”
Section: Introductionmentioning
confidence: 97%
“…[17][18][19][20] It is not clear from these studies if the ED led to female sexual dysfunction (FSD), if FSD led to male ED, or if there were other factors (for example relationship problems) that led to both ED and FSD. However, there is evidence that treatment of male ED has a positive effect on FSD.…”
Section: Introductionmentioning
confidence: 99%
“…2 While the physical component of ED has been well documented and has been further highlighted by the GBSS, 2 the psychological effects of ED can impact on both partners. [4][5][6] As ED also has negative impact on the sexual life of female partners (including reduced sexual activity 7 and reduced sexual satisfaction and sexual desire 8,9 ) it is important that healthcare providers include both partners in any discussions on sexual health issues.…”
Section: Introductionmentioning
confidence: 99%